Remodelling the Life Course: - Milka Satinovic (Grounded Theory Review: An International Journal, 2017)
The aim of the study was to develop a substantive grounded theory on how to live a life as good as possible with multiple sclerosis (MS). The question of how to improve the quality of life is of key importance when speaking of a chronic illness like MS. We still have little knowledge of this important question from the patients’ perspective. Classic grounded theory was used to explore patients’ experiences of living with MS. The aim was to identify their main concern and how they process this concern at different phases in their life course. Twenty-one interviews were conducted with 17 participants diagnosedwith multiple sclerosis. Participant observation at five courses for people with a multiple sclerosis diagnosis generated field notes. The participants’ main concern was how to live a life as good as possible in spite of their deteriorating health. The participants met this challenge through a process of remodelling the life course, in four phases: postponing (keeping up a normal life), adjusting (moving on to a changed life), restructuring (doing the best of it in a changed life), and transforming (preventing illness from controlling life). The remodelling process is influenced by the individual context, like the current health situation, biography, relations, and structural conditions. The process of remodelling helps us understand what facilitates and what hinders patients with MS from living a good life.